TRANSLATION OF THE ENGLISH TITLES INTO MACEDONIAN WITH AN EMPHASIS ON THE USE OF THE MARKERS OF DEFINITENESS - Vidova, Katerina (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The aim of this paper it to give an outline of the English titles of literature works, theater plays and films and their Macedonian translation equivalents with an emphasis on the use, or the omission of the markers of definiteness. The research is conducted on a corpus of English titles excerpted from catalogues of film and theater art and titles of literature works and their translation into Macedonian. We are focused on the use of the markers for the grammatical category definiteness. Analyzing the corpus of excerpted titles, similarities and differences regarding the use, or the omission of the markers for expressing the definiteness have been perceived. Keywords: title; translation; NP; markers; definiteness.